2009
DOI: 10.1097/ftd.0b013e3181c05adf
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Electrospray Ionization LC-MS/MS Method for Quantitative Analysis of Raltegravir, Etravirine, and 9 Other Antiretroviral Agents in Human Plasma Samples

Abstract: A rapid, specific, and sensitive LC-MS/MS method for quantification of raltegravir, etravirine, and 9 other antiretrovirals in human plasma was developed and was successfully applied for routine therapeutic drug monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
0
28
0
1
Order By: Relevance
“…This method is simple, reliable, and sensitive, using cost-effective instrumentation when compared with others. [5][6][7] However, this method requires a solid phase extraction. Furthermore, in general hospitals, a UV detector coupled with HPLC is more popular than a PDA detector.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…This method is simple, reliable, and sensitive, using cost-effective instrumentation when compared with others. [5][6][7] However, this method requires a solid phase extraction. Furthermore, in general hospitals, a UV detector coupled with HPLC is more popular than a PDA detector.…”
Section: )mentioning
confidence: 99%
“…Fayet et al 5) and Quaranta et al 6) succeeded in determining plasma concentrations of ETV and other drugs through the use of liquid chromatography-tandem mass spectrometry (LC-MS/MS). Rezk et al 7) have also developed a method to measure plasma concentrations of ETV and PIs by LC-MS. LC-MS or LC-MS/MS assay is very sensitive and accurate.…”
Section: )mentioning
confidence: 99%
“…A detailed literature survey for Etravirine revealed that various methods based on varied techniques namely LC-MS/MS [5][6][7][8], HPLC-MS [9,10], HPLC [11,12], and a direct UV-Visible spectrophotometric method for validation of Etravirine at 310 nm performed with equal ratio of acetonitrile and water as solvent, were reported [13]. The experimental results were applied for statistical analysis and found satisfactory precision and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…For example, (Heine et al, 2009) developed an LC-MS/MS method quantifying etravirine in human plasma, dry blood spot, and peripheral blood mononuclear cell lysate. LC-tandem MS methods were also available for simultaneous analysis of etravirine with other NNRTIs (Fayet et al, 2009;Else et al, 2010) in human plasma and with protease inhibitors (Quaranta et al, 2009). All the above referenced methods used a direct plasma protein precipitation using organic co-solvent and had etravirine detection limit of > 10 ng/mL, except for a study by (Rezk et al, 2009), where a 2 ng/mL detection limit was reported.…”
Section: Introductionmentioning
confidence: 99%